COMPARATIVE ANALYSIS OF PLATFORM LIABILITY FOR ILLEGAL PREMIUM ACCOUNT SALES: A STUDY OF SAFE HARBOR PRINCIPLES IN INDONESIA AND THE UNITED STATES - Ni Putu Ayu Meylan Ardini; Ni Ketut Supasti Dharmawan; Salwa Putri Hardiyan (Masalah-Masalah Hukum, 2025)
The rapid development of Indonesia’s digital economy has created new opportunities but also significant challenges, particularly regarding the illegal sale of shared premium accounts on e-commerce platforms. This study examines the legal frameworks governing platform liability for these illegal activities, comparing Indonesia’s regulations with the United States' Digital Millennium Copyright Act (DMCA). Using a doctrinal legal research method, the research focuses on key Indonesian laws such as the Copyright Law (Law No. 28 of 2014) and the Information and Electronic Transactions Law (ITE Law), alongside Section 512 of the DMCA. The study finds that Indonesia's legal framework provides only implicit protections, relying on general principles like good faith and fault-based liability, which leads to legal uncertainty. In contrast, the United States’ DMCA offers clearer protections through its Safe Harbor provisions, including a specific notice-and-takedown procedure. This comparative analysis highlights the vulnerability of Indonesian platforms to lawsuits and the broader economic consequences, such as lost revenue, hindered innovation, and potential reputational damage. Furthermore, it emphasizes the need for clearer, consolidated regulations in Indonesia to effectively protect copyright holders and digital platforms. The study proposes a Sui Generis Safe Harbor Model that combines the procedural clarity of the DMCA with Indonesia’s civil law tradition, including the establishment of clear Red Flag Knowledge standards, a mandatory notice-and-takedown procedure, and data disclosure requirements. The research underscores the importance of regulatory reform, enhanced law enforcement coordination, and technological investment to address illegal premium account sales and secure a fair digital environment.